Mozzarella cheese from recombined cow milk - Hamad, Mohamed Nour-Eldin farid; Abdel-Kader, Yehia Ibrahim; Elmetwally, Mohamed Mohamed (Indian Journal of Dairy Science, 2018)
To utilize the cow skim milk produced by small dairy plants, palm oil, Milk Protein Concentrate (MPC) and 3 emulsifiers were tried. 9 treatments were processed into Mozzarella cheese, first was whole cow milk (control), the second was whole cow milk+1.0% MPC. The third was cow skim milk+1.0 MPC+3.5% palm oil without emulsifiers, the fourth, fifth, sixth, seventh, eighth andÂ ninth treatments have the some recombined milk with 0.10 or 0.15% Lethecin (L), Tri-sodium citrate (TSC) and Di-sodium phosphate (DSP) were separately added. All processed cheese were stored at freeing conditions (-18Â°C) for 60 days Chemical, functional characteristic were periodically determined. Fresh and 60 days old cheese were organoleptically evaluated. Results showed the very important role of MPC in raising the yield and improving cheese quality. Among the three emulsifiers 0.15% (TSC) gave the highest yield and the higher organoleptic scoring points.